Obstacles to domestic and foreign investment in the Kingdom of Saudi Arabia - Alqnayah, Reem Abdullah (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the importance of local and foreign investment in the development of the national economy, determine the extent of the difference between local and foreign investors towards the obstacles they face in investments, reveal the obstacles to domestic and foreign investment in the Kingdom of Saudi Arabia, and identify the most important factors that contribute to finding optimal solutions to these obstacles. And the difficulties, the researcher relied on the use of the descriptive approach, and the target community was determined to consist of all local and foreign investors in the city of Riyadh, where the hypotheses of the study were weak legislation related to competition from legal and technological obstacles to local and foreign investment in Saudi Arabia, not providing that structure from legal and technological obstacles Local and foreign investment in Saudi Arabia, and low transparency and flexibility in the application of these laws are among the regulatory obstacles to local and foreign investment in Saudi Arabia. The results of the study showed weak legislation related to competition, lack of infrastructure for investment projects, low transparency in the application of regulations and the necessary inflexibility when implementing them, and some conflicting Current systems with systems As for foreign investment, the lack of incentives to invest in remote areas, the delay in disbursing dues to government agencies, and the length of customs exemption procedures, the study recommended increasing attention to competition-related legislation, providing the necessary infrastructure for investment projects, interest of government agencies in disbursing dues on time, transparency and flexibility in Applying investment laws and regulations, and providing investment facilities to investors in remote areas.
Keywords: foreign and domestic investment; types of investment; investment climate; economic growth